Involvement of Indigenous People In The Utilization of Natural Resources For Investment Activities - Sedubun, Victor Juzuf (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Constitutionally, Indigenous Peoples are 'subjects' of natural resources which are the rights of Indigenous Peoples that have been managed and maintained for generations based on their local wisdom. Indigenous Peoples must be involved in investment activities through the involvement of Indigenous Peoples from the beginning of the planning stage to provide input and other involvement in share ownership of investment or business activities.Purposes of the Research: This research was conducted with the aim of knowing and analyzing the form of fulfillment of the involvement of Indigenous Peoples in the implementation of investment activities.Methods of the Research: The research conducted is normative. For this reason, the problem approaches used are: a statutory approach, a conceptual approach, and a human rights-based approach. The sources of legal materials used consist of primary legal materials and secondary legal materials. And then the legal materials are collected for inventory and used in the analysis of the problems raised.Results of the Research: The fulfillment of the rights of Indigenous Peoples to customary territories and rights to manage natural resources in investment activities has not been fully realized. The government must ensure that the fulfillment of the rights of Indigenous Peoples in investment activities is accommodated and not violated in the preparation of laws and regulations. So that the legal certainty of the involvement of Indigenous Peoples in investment can be fulfilled, in the form of involvement from the planning stage to the implementation of the investment.